2010
DOI: 10.1007/s12264-010-6023-5
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β with learning and memory

Abstract: Abstract:Interleukin-1 (IL-1) is one of the first cytokines ever described. It has long been recognized to play an important role in mediating inflammation and orchestrating the physiological and behavioral adjustments that occur during sickness.Recently, accumulating evidence has indicated that IL-1 also adversely affects cognitive function. Nevertheless, there are also some reports showing no effects or even beneficial effects of IL-1 on learning and memory. The relationship between IL-1 and cognitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 110 publications
3
37
0
Order By: Relevance
“…Pro-inflammatory cytokines of the interleukin family play many diverse roles in development, maintenance and aging of the brain, and in particular, the hippocampus. Because of their involvement in plasticity, synaptic pruning, and neurogenesis (Arisi 2014; Graeber et al 2011; Huang and Sheng 2010; Yirmiya and Goshen 2011), it is premature to infer what aspect of IL-1β is central to the influence on hippocampal volume observed in this cross-sectional study. Although several longitudinal studies have confirmed the progressive (and probably accelerated) nature of age-related hippocampal shrinkage (see Raz and Kennedy 2009 for a review), at the time of this writing, there are no longitudinal studies of hippocampal subfield volumes in normal adults.…”
Section: Discussionmentioning
confidence: 95%
“…Pro-inflammatory cytokines of the interleukin family play many diverse roles in development, maintenance and aging of the brain, and in particular, the hippocampus. Because of their involvement in plasticity, synaptic pruning, and neurogenesis (Arisi 2014; Graeber et al 2011; Huang and Sheng 2010; Yirmiya and Goshen 2011), it is premature to infer what aspect of IL-1β is central to the influence on hippocampal volume observed in this cross-sectional study. Although several longitudinal studies have confirmed the progressive (and probably accelerated) nature of age-related hippocampal shrinkage (see Raz and Kennedy 2009 for a review), at the time of this writing, there are no longitudinal studies of hippocampal subfield volumes in normal adults.…”
Section: Discussionmentioning
confidence: 95%
“…It is not clear if there is complex interplay between these different subunits, which could manifest in altered mouse behavior. It may also explain why many controversial results were observed for the IL-1 study45. Moreover, AIM2 is just one of various inflammasome sensors that processes pro-IL-1β and Aim2 deletion can only impair IL-1β production in response to dsDNA and perhaps only in a subset of cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Under experimental conditions, IL-1β mRNA expression occurs mainly within cortical regions (parietal and frontal cortex), hippocampus, hypothalamus, thalamic nuclei, pituitary gland and cerebellum after administration of LPS (Eriksson et al, 2000;Gabellec et al, 1995). Injection of IL-1β results in impairment of hippocampal-dependent learning and memory as well as long-term potentiation in animal models (Huang and Sheng, 2010). Emerging evidence also indicates the involvement of IL-1β in neurogenesis (McAfoose and Baune, 2009).…”
Section: Il-1βmentioning
confidence: 99%